SEBUAH ANALISIS SEMIOTIK LOGO KOKO CICI INDONESIA - Christina Christina (SEMIOTIKA: Jurnal Komunikasi, 2016)
‘Koko Cici Indonesia’ was pioneered by Koko Cici Jakarta election held in 2002. Koko Cici Jakarta was born with the aim of increasing inclusiveness Indonesian youths in Chinese culture as part of the wealth of Indonesia. The purpose of this study to determine the meaning of the logo Koko Cici Indonesia as well as knowing the representation and the strengthening of the identity on the logo Koko Cici Indonesia. This research method by analyzing use semiotics of Charles Sanders Peirce basis of sign, qualitative research, with representation and identity theory. Finding shows that the representation of Koko Cici Indonesia logo through competency standards, the provision of knowledge and objectives, have the same understanding to become Koko Cici and become cultural ambassador of Tionghoa, Indonesia tourism ambassador and social ambassador will support identity as Koko Cici Indonesia, Koko Cici is supported with cheongsam and qibao for their duty, greetings, and sash into a unity identity of Koko Cici Indonesia. The identity you want to display from this logo is Koko Cici is not exclusive but they have unity diversity based on the meaning of ba gua’, also maintain the harmonization of tradition. From the logo Koko Cici Indonesia also shows as a Chinese organization seen from the symbol of Dragon & Phoenix, as well as large capacity due to logo like umbrella.Key Words: Semiotic, Peirce, Logo, Representative, Identity, Communication